2013
DOI: 10.1016/s1470-2045(13)70035-4
|View full text |Cite|
|
Sign up to set email alerts
|

Axillary dissection versus no axillary dissection in patients with sentinel-node micrometastases (IBCSG 23–01): a phase 3 randomised controlled trial

Abstract: Background For breast cancer patients with a metastatic sentinel node (SN), axillary dissection (AD) has been standard treatment. However, for patients with minimal SN involvement, AD may be overtreatment. IBCSG Trial 23-01 was designed to determine whether no AD is non-inferior to AD in patients with one or more micrometastatic (≤2 mm) SNs and tumour ≤5 cm. Methods In this multicentre trial patients were randomised to AD or no AD. Eligibility was limited to patients with clinically-palpable axillary lymph n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
684
5
39

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,083 publications
(758 citation statements)
references
References 26 publications
30
684
5
39
Order By: Relevance
“…The omission of further surgery for these patients is thus warranted given that there has now been a strong move away from clearing for micro metastases identified by standard techniques. The sensitivities reported here for the detection of both micro and macro-metastases (23% to 29%) are at the lower end of those previously published [14] [15]. This may reflect the fact that the dataset includes micro-metastases within the positive node group.…”
Section: Discussioncontrasting
confidence: 58%
“…The omission of further surgery for these patients is thus warranted given that there has now been a strong move away from clearing for micro metastases identified by standard techniques. The sensitivities reported here for the detection of both micro and macro-metastases (23% to 29%) are at the lower end of those previously published [14] [15]. This may reflect the fact that the dataset includes micro-metastases within the positive node group.…”
Section: Discussioncontrasting
confidence: 58%
“…It is unclear whether these patients may have derived less benefit from an ALND, masking the benefit of ALND in patients with a greater burden of nodal disease. The recently published IBCSG 23-01 trial, looking specifically at patients with micrometastatic disease in their sentinel lymph nodes, lends support to this theory 11 . This study concluded that axillary dissection could be avoided in patients with early stage breast cancer and limited sentinel-node involvement without an adverse effect on survival.…”
Section: Discussionmentioning
confidence: 92%
“…as the "standard of care" in clinically node negative (cN0) disease and no further treatment of the axilla is advised in cases of a negative SLN, or when it contains isolated tumour cells or a micro-metastasis as there is no benefit in terms of disease free survival (DFS) or overall survival (OS) [5].…”
Section: Management Of the Axilla In Clinically Node Negative Diseasementioning
confidence: 99%